2014
DOI: 10.1186/preaccept-3233957281325201
|View full text |Cite
|
Sign up to set email alerts
|

First identification of proteins involved in motility of Mycoplasma gallisepticum

Abstract: Mycoplasma gallisepticum, the most pathogenic mycoplasma in poultry, is able to glide over solid surfaces. Although this gliding motility was first observed in 1968, no specific protein has yet been shown to be involved in gliding. We examined M. gallisepticum strains and clonal variants for motility and found that the cytadherence proteins GapA and CrmA were required for gliding. Loss of GapA or CrmA resulted in the loss of motility and hemadsorption and led to drastic changes in the characteristic flask-shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…A previous study shows that the adhesin complexes of M. pneumoniae exist around the membrane protrusion (7). M. gallisepticum may have a similar distribution because it uses similar gliding machinery to M. pneumoniae (36-39). The distribution of adhesin complexes suggests that cells may roll around the cell axis during gliding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study shows that the adhesin complexes of M. pneumoniae exist around the membrane protrusion (7). M. gallisepticum may have a similar distribution because it uses similar gliding machinery to M. pneumoniae (36-39). The distribution of adhesin complexes suggests that cells may roll around the cell axis during gliding.…”
Section: Resultsmentioning
confidence: 99%
“…Mycoplasma gallisepticum is an avian pathogen that causes chronic respiratory disease in chickens and infectious sinusitis in turkeys. The cells transmit from breeder birds to their progeny in ovo (1, 35, 36). M. gallisepticum glides using the M. pneumoniae -type motility system and has eight homologs of component proteins of gliding machinery in M. pneumoniae whose identities for amino acids range from 20% to 45% (36-39).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the description of the case, four points were denoted by Prof. Dodd as distinctive between both cases, concluding that the two reports were describing different microorganisms [ 52 ]. However, unraveling these four points based on the current knowledge about MG, it can be concluded that, certainly, the first outbreak related to MG was described in the report by Prof. M’Fadyean in 1893 [ 53 ], since it is well known that MG is a motile mycoplasma [ 13 ] that causes adhesive pericarditis and it is not related with enteritis [ 54 ]. The closeness among the estimated values (Bayesian estimation) and the historical record about the emergence of MG are indicative of the accuracy and reliability of the methodology used and also suggest that the emergence of MG as a relevant pathogen in poultry is linked to the evolutionary events in the mgc2 gene.…”
Section: Resultsmentioning
confidence: 99%
“…This property has been linked to the gliding motility mechanism, providing MG with an adaptative advantage. A recent report by Indikova et al (2014) identified the mgc2 gene within the mgc locus involved in the motility of MG, highlighting the role of this gene as a key virulence factor of MG [ 13 ].…”
Section: Introductionmentioning
confidence: 99%